P130 Dynamic hyperinflation is associated with a poor cardiovascular response to exercise in COPD patients. (2nd December 2011) - Tzani, P; Aiello, M; Elia, D; Boracchia, L; Marangio, E; Olivieri, D; Clini, E; Chetta, A
Abstract : Background: Pulmonary hyperinflation has the potential for significant adverse effects on cardiovascular function in COPD. The aim of this study was to investigate the relationship between dynamic hyperinflation and cardiovascular response to maximal exercise in COPD patients. Methods: We studied 48 patients (16F; age 68 yrs ±8; BMI 26±4) with COPD. All patients performed spirometry, plethysmography, Lung diffusion capacity for carbon monoxide (TLco) measurement, and symptom-limited cardiopulmonary exercise test (CPET). The end-expiratory lung volume (EELV) was evaluated during the CPET. Cardiovascular response was assessed by change during exercise in oxygen pulse (ΔO2 Pulse) and double product, that is, the product of systolic blood pressure and heart rate (DP reserve), and by the oxygen uptake efficiency slope (OUES), that is, the relation between oxygen uptake and ventilation. Results: Patients with a peak exercise EELV (%TLC) ≥75% had a significantly lower resting FEV1 /VC, FEF50 /FIF50 ratio and IC/TLC ratio, when compared to patients with a peak exercise EELV (%TLC) <75%. Dynamic hyperinflation was strictly associated to a poor cardiovascular response to exercise: EELV (%TLC) showed a negative correlation with ΔO2 Pulse ( r = − 0.476, p = 0.001), OUES ( r = − 0.452, p = 0.001) and DP reserve ( r = − 0.425, p = 0.004). Furthermore, according to the ROC curve method, the EELV (% TLC) cut-off point which maximised sensitivity and specificity, with respect to a DP reserve value <10 000 as threshold value, was ≥75 % (0.76 sensitivity and 0.80 specificity). Conclusion: The present study shows that COPD patients with dynamic hyperinflation have a poor cardiovascular response to exercise. This finding supports the view that in COPD patients, dynamic hyperinflation may affect exercise performance not only by affecting ventilation, but also cardiac function.